Increasing the share of non–cash payments and settlements in the Kyrgyz Republic - A. M. Maratov; К. А. Ajekbarov (Путеводитель предпринимателя)
The paper considers the payment system of the Kyrgyz Republic in the light of integration into the EAEU. The development of non–cash payment markets in the EAEU member states differs significantly. The level of development of the payment system in Kyrgyzstan is not high; significantly higher levels of this branch development in the union are noted in Russia and Kazakhstan.